2019
DOI: 10.1177/0020764019850204
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of internalized stigma levels in people with psychosis in the Czech Republic

Abstract: Background: Internalized stigma negatively affects lives and prognosis of individuals with psychosis. Aim: This study aimed to identify correlates of internalized stigma among individuals with psychosis in a sample of community care users in the Czech Republic. Methods: A cross-sectional study was conducted among 133 community service users with psychosis. A shortened version of the Internalized Stigma of Mental Illness (ISMI-10) scale was used alongside the 5-level EQ-5D version (EQ-5D-5L), assessing health-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…This finding is in line with a study from China conducted among severe mental disorders in rural communities using the same tool for measuring stigma [25]. However, this estimate is higher compared to most other studies within Nepal [15,17] and other parts [8,28] of the world. Studies comparing stigma scores within diagnostic categories have persistently reported higher self-stigma scores for schizophrenia and psychosis compared to affective disorders and this could be the main reason behind the discrepancy reported [25,29].…”
Section: Plos Onesupporting
confidence: 89%
See 3 more Smart Citations
“…This finding is in line with a study from China conducted among severe mental disorders in rural communities using the same tool for measuring stigma [25]. However, this estimate is higher compared to most other studies within Nepal [15,17] and other parts [8,28] of the world. Studies comparing stigma scores within diagnostic categories have persistently reported higher self-stigma scores for schizophrenia and psychosis compared to affective disorders and this could be the main reason behind the discrepancy reported [25,29].…”
Section: Plos Onesupporting
confidence: 89%
“…On the other hand, too long duration as more than 10 years could mean patients have adjusted somehow to their diagnosis leading to less stigma as reported in this study. Results reporting positive correlations of duration of illness with ISMI scores have been reported in a number of studies [8,[12][13][14]. These differences could be because the first study was conducted among all outpatients with mental illness and not only schizophrenia, the second study among severe mental illnesses, including schizophrenia, schizoaffective disorder, and bipolar disorder while the third study was conducted among psychosis in community setting, rather than in hospital setting.…”
Section: Plos Onementioning
confidence: 90%
See 2 more Smart Citations
“…Mental health care remained institutionalized [15], economically ineffective [16,17], and problematic from a human rights perspective [18]. Attitudes towards those with mental illness have been unfavourable among the general population as well as among medical doctors or students [5,6,19], and people with mental health problems and their relatives often feel that they are targets of stigma and discrimination [20,21].…”
Section: Introductionmentioning
confidence: 99%